2017
DOI: 10.1080/00325899.2017.1280647
|View full text |Cite
|
Sign up to set email alerts
|

Contamination in wet-ball milling

Abstract: The top-down approach of mechanical ball milling/alloying is the most commonly adopted route towards materials development. It is however surprising that despite the large impact that it has, process induced contamination (particularly from process control agents (PCAs)), remains less studied and often ignored. In this article, a theory that explains the cause of PCA-induced contamination is postulated. An attempt is then made through reviewing the literature to reason why there is ignorance. Influence of cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In the case when one mills two different metallic powders, several solid phase transformations take place [12,13,14,15]. A process control agent (PCA) such as stearic acid, benzene, methanol, or ethanol is added to the powder mixture during milling to reduce the effect of cold welding between powder particles [16,17,18]. The PCA adsorbs on the surface of the powder particles and minimizes cold welding between powder particles and thereby inhibits agglomeration [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case when one mills two different metallic powders, several solid phase transformations take place [12,13,14,15]. A process control agent (PCA) such as stearic acid, benzene, methanol, or ethanol is added to the powder mixture during milling to reduce the effect of cold welding between powder particles [16,17,18]. The PCA adsorbs on the surface of the powder particles and minimizes cold welding between powder particles and thereby inhibits agglomeration [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In some Fe containing powder milling, it was found that the presence of organic PCA, except ethanol, was necessary for the formation of the amorphous phase. This fact was explained by the dissolution of C atoms from PCA in the Fe-B phase by mechanical milling [18,23]. The role of ethanol in the formation of amorphous structure is not clear during high-energy milling of the Al matrix powders either.…”
Section: Introductionmentioning
confidence: 99%
“…This may affect the different degree of contamination of composites with the dope coming from the used grinding balls (Al 2 O 3 ) and the blades in the attritor (ZrO 2 ). This contamination may also cause changes in theoretical density, which will affect the theoretical density of composites, and thus affect the density of the measured relative density [ 27 , 28 ]. The microstructure analysis also shows that, regardless of the mill used in the technological process, the Ti 3 AlC 2 phase distributed among the matrix grains effectively reduces the growth of the Al 2 O 3 matrix grain in relation to the reference sample.…”
Section: Discussionmentioning
confidence: 99%
“…This operation should conveniently be carried out under a protective atmosphere (e.g., inside atmosphere‐controlled glove boxes) when reactive powders are employed, to avoid their oxidation and contamination (see Section 3.1). Process control agents are sometimes added to the milling mixture, mostly to minimize particle agglomeration by acting as lubricants or surfactants [18] . Then, the grinding jar is sealed and secured with clamps inside the mill, where the milling is carried out for the desired time at an appropriate milling frequency.…”
Section: General Aspects Of Ball Millingmentioning
confidence: 99%